Primary identification of an abused child in dental office: A case report - Santos J; Cavalcanti A; Nunes K; Silva E (Wolters Kluwer Medknow Publications, 2007)
Although the injuries of child abuse are many and varied, several types of injuries are common to abuse. Many of these injuries are within the scope of dentistry or easily observed by the dental professional in the course of routine dental treatment. The authors present a case of child abuse with multiple bruises. The child had been spanked in the previous night and the morning of the attendance by his mother. This case emphasized that all practitioners should be vigilant when patients present with abnormal injuries which may be the result of abuse and further investigation should be instigated.